Stress and burnout syndrome for healthcare personnel - Rus, Mihaela; Sandu, Mihaela Luminita; Marinescu (Leoca), Oana; Pavel (Belgun), Madalina; Stoica (Ciuca), Corina (Technium Social Sciences Journal, 2022)
Stress is one of the most common problems nowadays. Numerous studies have been done, books have been written and yet stress remains a topical issue. In this age of speed, when everything is running fast forward, both the quality of life and the state of health are negatively affected by stress. As the father of stress, Selye (1974), puts it, life itself is stressful. Whether it is stress at the level of the individual or the organization, the confrontation with the stressor factors offers the possibility to adapt to the new conditions and the development of coping mechanisms